Professional ethics at the international bar - Sarvarian, Arman (Oxford : Oxford University Press, 2014)
The number of practitioners appearing before international courts, tribunals, and arbitral panels has risen sharply in the last decade, prompting concerns over ethics and best practice standards. This book assesses these issues, and argues that common ethical standards will be key to maintaining the integrity of the international judicial system.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 13, 2013).
Keywords: Legal ethics; International courts; Procedure (Law)